Assessment of factors connected with radiotherapy influencing the cosmetic effect in breast conserving therapy - Błaszczyk, Piotr; Roszkowski, Krzysztof; Błaszczyk, Ewelina; Kowalewski, Janusz (Contemporary Oncology/Współczesna Onkologia, 2009)
Aim: To compare cosmetic results of different radiotherapy schedules used in the treatment of breast cancer after breast radiotherapy and to identify factors affecting cosmetic outcomes. Material and methods: Nainty-four patients irradiated. Median follow-up of 29 months (ramge 18-154 mo.). Patients were treated with standard fractionation 45-50 Gy/20-25 fx/4-5 weeks. Boost up to 10 Gy. Late effects were evaluated using the LENT-SOMA scoring scale. The cosmetic results were assessed on a four-point scale and presence of concomitant chemotherapy. Results: LENT-SOMA grade 3 toxicity was observed only in 8 (8,5%) patients. The factor associated with hyperpigmentation is large breast size. The significant risk factors for teleangiectasia are high dose and use foton energy 1,33 MeV beam. Factors found to impact significantly cosmesis adversely fibrosis was large breast size. Breast fibrosis were more frequent observed in woman after whole dose 50 Gy. There were no differences in breast skin thick between analysed factors. Conclusions: After irradiating large breasts more often than one observes the fibrosis of the breast in the case of small and average breasts and discoulour of the skin. Irradiating photons from the cobalt source in the comparison with photons about higher energy at women with large breasts, there is the reason more frequent occurrence of the skin angioma. For the final cosmetic effect of radiotherapy in saving treatment, they do not have the impact: tumor size, boost method, chemical treatment, patients age.